ACRL Framework in Information Literacy in Mathematics and Statistics Class: What Students of Mathematics Think about It?. Issue 1 (2nd January 2019) - Holden, Irina I.
ABSTRACT: The Association of College and Research Libraries (ACRL) Framework for Information Literacy, based on threshold concepts, has become the important source for guidance for instruction librarians in planning their classroom instruction. The author describes her experience in introducing students to the Framework in her one-credit Information Literacy in Mathematics and Statistics course. Students were assigned a reflective exercise, in which they had to read the text of one of the six frames from the Framework, and then try to relate their research experience to the knowledge practices and dispositions. Afterward, students wrote paragraph-long reflections. Analyzing these reflections enhanced the instructor's understanding of the Framework and helped her formulate new possibilities for using the Framework in the future.